ANALISIS PENENTUAN KLASIFIKASI NILAI KANDUNGAN GIZI PADA MAKANAN DAN MINUMAN INSTAN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING BERBASIS WEBSITE SEBAGAI ALTERNATIF PENCEGAHAN DIABETES MELITUS - Imron Rosadi; Sujatmiko, Bambang; Tanhella Zein Vitadiar; Setyo Permadi, Ginanjar (Fakultas Teknologi Informasi, 2024)
This study applies the Simple Additive Weighting (SAW) method to select healthy instant food andbeverage products to prevent Diabetes Mellitus. The developed web-based system evaluates nutritionalcriteria such as energy, sugar, saturated fats, sodium, fruits and vegetables, protein, and fiber. This systemassists consumers in making healthier food choices and supports efforts to prevent Diabetes Mellitus. It isalso expected to contribute to public health improvement through better nutritional education.Keywords: Simple Additive Weighting (SAW), Instant food and beverage products, Diabetes Mellitusprevention, Nutritional criteria, Web-based system, Healthier food choices, Public health, Nutritionaleducation.